2018
DOI: 10.1042/bsr20171014
|View full text |Cite
|
Sign up to set email alerts
|

High glucose contributes to the proliferation and migration of non-small-cell lung cancer cells via GAS5-TRIB3 axis

Abstract: Despite the growing number of studies exhibiting an association of diabetes mellitus (DM) and lung cancer progression, the concrete mechanism of DM aggravating lung cancer has not been elucidated. The present study was to investigate whether and how high glucose (HG) contributes to the proliferation and migration of non-small-cell lung cancer (NSCLC) cells in vitro. In the present study, we confirmed that HG promoted the proliferation and migration of NSCLC cells, and also induced an anti-apoptotic effect on N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 27 publications
(27 reference statements)
1
14
0
Order By: Relevance
“…48 GAS5 inhibited the high glucose (HG)-induced proliferation, anti-apoptosis, and migration of PC-9 and H1299 NSCLC cells through degradation of tribbles pseudokinase 3 (TRIB3) protein by ubiquitination, indicating that GAS5/TRIB3 might be novel targets for the prevention and treatment of diabetic NSCLC. 121 In addition, exogenously expressed GAS5 repressed cell proliferation and invasion and enhanced the radiosensitivity of NSCLC cells in vitro and in vivo by suppressing miR-135b expression, which deepens our understanding of the mechanism of miRNA-lncRNA interaction and providing a potential therapeutic for patients with NSCLC. 43 Moreover, GAS5 inhibited the proliferation and colony formation capability of NSCLC cells and induced the sensitivity of DDP in NSCLC via GAS5/miR-21/PTEN regulatory pathway.…”
Section: Molecular Mechanismsmentioning
confidence: 98%
“…48 GAS5 inhibited the high glucose (HG)-induced proliferation, anti-apoptosis, and migration of PC-9 and H1299 NSCLC cells through degradation of tribbles pseudokinase 3 (TRIB3) protein by ubiquitination, indicating that GAS5/TRIB3 might be novel targets for the prevention and treatment of diabetic NSCLC. 121 In addition, exogenously expressed GAS5 repressed cell proliferation and invasion and enhanced the radiosensitivity of NSCLC cells in vitro and in vivo by suppressing miR-135b expression, which deepens our understanding of the mechanism of miRNA-lncRNA interaction and providing a potential therapeutic for patients with NSCLC. 43 Moreover, GAS5 inhibited the proliferation and colony formation capability of NSCLC cells and induced the sensitivity of DDP in NSCLC via GAS5/miR-21/PTEN regulatory pathway.…”
Section: Molecular Mechanismsmentioning
confidence: 98%
“…The cells were cultured in DMEM containing high glucose (HG; 25 mM) or normal glucose (NG; 5 mM) with 10% foetal bovine serum, penicillin (100 U/mL) and streptomycin (100 U/mL) at 37°C in a 5% CO 2 humidified incubator (Thermo Fisher). HG treatment was used to induce the model of DM combined with A549 for 24 h. 22…”
Section: Cell Culturementioning
confidence: 99%
“…In the study of Zhang X et al, pseudokinase can activate the b-catenin signal pathway, which in turn promotes the proliferation and migration of NSCLC cells (Zhang et al, 2019). In addition, blocking the activity of TRIB3 may be one of the mechanisms for the treatment of lung cancer (Ding et al, 2018). Wang X et al have found that PAK4 is significantly associated with poor prognosis of NSCLC (Wang et al, 2016b), and LIMK1 phosphorylation mediated by it regulates the migration and invasion of NSCLC.…”
Section: The Biological Significance Of the Selected Genes In Lung Camentioning
confidence: 99%